Meningkatkan Prestasi Dan Motivasi Belajar Siswa Dengan Pengajaran Berbasis Inkuiri Pada Siswa Kelas VII.3 SMP Negeri 2 Peusangan Bireuen - Meutiana Meutiana (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2015)
In learning something well, we need to listen, look and ask the question about it and discuss it with others. Not only that, students need to â€œdoâ€ it, such as by describing something with their own ways, showing the examples, trying to apply the skills and doing the tasks which need the acquired knowledge. The problems examined in this study were (a) How is the increase of studentsâ€™ achievement by using the inquiry based instruction? (b) How is the influence of the inquiry based instruction towards studentsâ€™ motivation? The purposes of this study were (a) to determine studentsâ€™ understanding and achievement in Natural Sciences subject after conducting the inquiry based instruction, (b) to determine the influence on studentsâ€™ motivation by using the inquiry based instruction. The three-cycle class room action research design was used in this study. Each cycle consists of four stages namely: planning, observing, reflection and revision.The subject in this research was students of Class VII.3 of SMP Negeri 2 Peusangan. The data obtained were formative test results and the observation sheets of teaching-learning activities. Based on the findings, it can be seen that studentsâ€™ achievement increased from cycle I (65%) to cycle II (91 %). The conclusion of this study was the inquiry basedinstructionpositively influenced studentsâ€™ motivation of Class VII.3 of SMP Negeri 2 Peusangan. In addition, the inquiry basedinstruction can be used as one of alternative learning methods in Natural Sciences. Kata Kunci: prestasi belajar, model inkuiri.